A Prospective Study Evaluating Cumulative Incidence and a Specific Prediction Rule in Pulmonary Embolism in COVID-19 - Suarez Castillejo, Carla; Toledo-Pons, Nuria; Calvo, Néstor; Ramon-Clar, Luisa; Martínez, Joaquín; Hermoso de Mendoza, Sara; Morell-García, Daniel; Bauça, Josep Miquel; Berga, Francisco; Núñez, Belén; Preda, Luminita; Sauleda, Jaume; et al. (Frontiers in Medicine, 2022)
Rationale. Abnormal values of hypercoagulability biomarkers, such as D-dimer, have been described in Coronavirus disease 2019 (COVID-19), which has also been associated with disease severity and in-hospital mortality. COVID-19 patients with pneumonia are at increased risk of pulmonary embolism (PE). However, real incidence of PE is not clear yet, since studies have been limited in size, mostly retrospective, and performing PE diagnostic procedures only when PE was clinically suspected. Objectives. (1) To determine the incidence, clinical, radiological, biological characteristics, and clinical outcomes of PE among patients hospitalized for COVID-19 pneumonia with D-dimer >1000 ng/mL. (2) To develop a prognostic model to predict PE in these patients. Methods. Single-center prospective cohort study. Consecutive confirmed cases of COVID-19 pneumonia with D-dimer >1000 ng/mL underwent a computed tomography pulmonary angiography (CTPA). Demographic and laboratory data, comorbidities, CTPA scores, administered treatments, and clinical outcomes were analyzed and compared between patients with and without PE. A risk score was constructed from all these variables. Results. Between April 6th 2020 to February 2nd 2021, 179 consecutive patients were included. The overall incidence of PE was 39.7% (71 patients) (CI 95%, 32-47%). In patients with PE, emboli were located mainly in segmental/subsegmental arteries (67%). Patients with PE did not differ in gender, age, or risk factors for thromboembolic disease from the non-PE group. Higher urea, D-Dimer, D-dimer-to-ferritin and D-dimer-to-LDH ratios, platelet distribution width (PDW), and neutrophil-to-lymphocyte ratio (NLR) values were found in PE patients compared to non-PE patients. Besides, lymphocyte counts resulted lower in PE patients. A PE prediction score was constructed with an excellent overall performance (AUC-ROC 0.81 (95% CI: 0.73-0.89)). PATCOM score stands for Pulmonary Artery Thrombosis in COvid-19 Mallorca, and included the platelet count, PDW, urea concentration and D-dimer-to-ferritin ratio. Conclusions. Patients with COVID-19 pneumonia and D-dimer values >1000 ng/mL presented a very high incidence of PE, regardless of clinical suspicion. Significant differences in urea, D-dimer, PDW, NLR, and lymphocyte count were found between PE and non-PE patients. The PATCOM score is presented in this study as a promising prediction PE rule, although validation in further studies is required.